Early innate cell interactions with Mycobacterium tuberculosis in protection and pathology of tuberculosis - Sankar, Poornima; Mishra, Bibhuti Bhusan (Frontiers in Immunology, 2023)
Tuberculosis (TB) remains a significant global health challenge, claiming the lives of up to 1.5 million individuals annually. TB is caused by the human pathogen Mycobacterium tuberculosis (Mtb), which primarily infects innate immune cells in the lungs. These immune cells play a critical role in the host defense against Mtb infection, influencing the inflammatory environment in the lungs, and facilitating the development of adaptive immunity. However, Mtb exploits and manipulates innate immune cells, using them as favorable niche for replication. Unfortunately, our understanding of the early interactions between Mtb and innate effector cells remains limited. This review underscores the interactions between Mtb and various innate immune cells, such as macrophages, dendritic cells, granulocytes, NK cells, innate lymphocytes-iNKT and ILCs. In addition, the contribution of alveolar epithelial cell and endothelial cells that constitutes the mucosal barrier in TB immunity will be discussed. Gaining insights into the early cellular basis of immune reactions to Mtb infection is crucial for our understanding of Mtb resistance and disease tolerance mechanisms. We argue that a better understanding of the early hostpathogen interactions could inform on future vaccination approaches and devise intervention strategies.